GMO IS THE MAIN REASON PRODUCTS APPEAR. DAIRY PRODUCTS WITH GMO. WHAT IS GMO ITSELF? IS IT HARMFUL OR USEFUL? - Tosheva Durdona Omon qizi; Prof. Akramova Rano Ramizitdinovna (American Journals, 2023)
How GMO occurs in dairy products: Maquaculture provides advice on what gene-modified organisms are, why they are created, how they are created, their advantages, their harms, and how to avoid damage from gene-modified organisms.
Keywords: GMO, DNA, gene, human, plant varieties, animal breeds, components, diseases, advantages, disadvantages, dairy products.